Two different Xylella fastidiosa strains circulating in Italy: phylogenetic and evolutionary analyses. Issue 1 (1st January 2018) - Cella, Eleonora; Angeletti, Silvia; Fogolari, Marta; Bazzardi, Riccardo; De Gara, Laura; Ciccozzi, Massimo
ABSTRACT: Xylella fastidiosa, a bacterial species infecting a broad range plants, includes five subspecies, fastidiosa, multiplex, pauca, mulberry and sandyi. In Europe, Xylella was isolated in olive trees in southern Italy (Apulia region) during the year 2013. The aim of the present study was to apply phylogenetic and evolutionary analysis to trace the possible origin and way of the entrance of Xylella fastidiosa in Italy. All the genomes available for Xylella fastidiosa spp were downloaded from NCBI. A phylogeographic analysis was performed using BEAST. X. fastidiosa strains belonging to X. fastidiosa subsp. pauca and subsp. sandyi have been reported to infect olive trees and coffee plants, respectively. The phylogeographic analysis also revealed and confirmed these two different ways of provenience X. fastidiosa subsp. pauca from Costa Rica and X. fastidiosa subsp sandyi from California Phylogeny have been an important tool to validate and support the recent hypothesis for X. fastidiosa pauca provenience.